An investigation of the mission, vision, funding strategies and student services for distance learning in land grant and state universities - Thomas, Susan Peterson (Kansas State University, 2005)
This study was an investigation of mission, vision, funding strategies, and student services for distance learning as expressed by university administrators in land grant universities and state universities, and those institutions that are designated as both land grant and state universities by the state legislature. Three research questions guided the study The study employed a survey distributed through e-mail. The questionnaire was sent to 261 senior administrators; the chief academic officers, chief business officers, and chief information officers in 37 land grant and state universities and 13 institutions that are both land grant and state universities. The return rate was 30%. The institutional mission and administrator’s vision for offering distance learning survey responses were analyzed using descriptive statistics. The study also used correlation, confirmed by factor analysis, to determine if there was a relationship among the administrators’ responses regarding mission, vision, and funding. The data were analyzed with ANOVA and fishers least means difference test. These tests determined if there were differences in the administrators’ responses between the type or sizes of higher education institutions on mission, vision of administrators. The data analysis indicated that the type of institution did not yield significant differences. The difference of means test indicated there were differences in the student population size of the institutions. The responses indicated the mission or purpose for offering distance learning was to save money for the institution, and support degree completion for former students. The responses related to administrative vision show initiating a distance learning program and a being leader among higher education institutions were the reasons for a distance learning program. The content analysis method was employed to determine the roles of the administrators in the survey. The administrators’ responses related to distance learning were consistent with their roles in the institution. The study also produced results related to student services institutions provide for distance learning students, how the student services were provided, on or off campus or both locations and the funding sources for the student services.
Keywords: Distance learning; Distance learning and mission; Distance learning funding; Distance learning senior administrators; Distance learning land grant universities; Distance learning student services; Education, Curriculum and Instruction (0727)